Extractive Composition of Mangium Wood (Acacia mangium) - Ganis Lukmandaru (Jurnal Ilmu dan Teknologi Kayu Tropis, 2012)
The objective of this research is to find out the extractive composition of mangium wood. A total of 25 mangium trees (24-years) from 5 provenances (Sidei Papua, West of Morehead, Daintree, Ellerbeck, Red Cardwell, and El Arish) were investigated. The extractive contents were determined by successive soxhlet extraction in two solvents (n-hexane and methanol). The results showed that the effect of provenance factor is not significant by analysis of variance. The range of n-hexane extracts were 1-6% which the highest value was obtained in the heartwood whereas methanol extracts ranged from 3-18% as the highest value was measured in the bark. In the n-hexane extracts based, neutral fractions dominated (80-95%) the composition the sapwood and heartwood. After saponification, the similar tendency was also observed which the unsaponifiables (60-80%) composed the most part in the neutral fraction of sapwood and heartwood. In the methanol extracts based, residue fractions (55-65%) composed the most part in the bark while dichloromethane fractions were comparatively high (30-41%) in the sapwood parts. In the heartwood, buthanol and residue fractions dominated (15-77%) in considerable varied patterns. Differences due to provenance factor was also observed, both in the n-hexane and methanol extract fractions.Key words: Acacia mangium, extractives, provenance, radial direction